Comparative Microbiological Assessment of Drinking Water Collected from Different Areas of Kathmandu Valley (Tribhuvan University Journal of Microbiology, 2019)
Objectives: This study was aimed to evaluate different water samples in terms of Total bacterial load and Total Coliform Load in comparison with different parameters such as pH, type of samples, chlorination status, turbidity, temperature and collection areas.Methods: Altogether 250 water samples were collected; 110(44%) were ground water samples, 60(24%) were public tap water samples and 80(32%) were bottled water samples. Total Coliform load was evaluated using Membrane Filtration Technique and Total Bacterial Load was evaluated using Aerobic Plate Count Technique. pH was measured using pH meter, turbidity was measured using nephelometer, temperature was measured using temperature probe and bottled water were considered chlorinated.Results: Among these 250 samples, the highest mean bacterial load was seen in public tap water samples (137×103 cfu/ml) and least mean bacterial load was seen on bottled water sample (28×103). Similarly, highest mean coliform load was seen on ground water samples (81 cfu/ml) and least mean coliform load was seen on bottled water samples (6 cfu/ml).Conclusion: This study has concluded that ground water samples contain large number of coliforms which suggest it might be fecally contaminated. Also the result had shown even bottled water contained coliforms. Therefore, it is recommended to treat ground water before using. Proper care must be taken during manufacture of bottled water.